Psychophysiological responses to virtual crowds: Implications for wearable computing - Christou, Chris; Herakleous, Kyriakos; Tzanavari, Aimilia; Poullis, Charalambos (My University, 2015)
Human responses to crowds were investigated with a simulation of a busy street scene using virtual reality. Both psychophysiological measures and a memory test were used to assess the influence of large crowds or individual agents who stood close to the participant while they performed a memory task. Results from most individuals revealed strong orienting responses to changes in the crowd. This was indicated by sharp increases in skin conductance and reduction in peripheral blood volume amplitude. Furthermore, cognitive function appeared to be affected. Results of the memory test appeared to be influenced by how closely virtual agents approached the participants. These findings are discussed with respect to wearable affective computing which seeks robust identifiable correlates of autonomic activity that can be used in everyday contexts.
Keywords: Affect; Blood volume pulse; Cognitive function; Crowds; Proxemics; Psychophysiology; Skin conductance